PENGARUH ABILITY PEGAWAI MEMAHAMI ISU-ISU LINGKUNGAN DAN KEPEMIMPINAN TERHADAP PENGELOLAAN KONSERVASI HUTAN KOTA - Rusdi Hidayat; Suwirman Nuryadin; Muzani Jalaludin (Jurnal Green Growth dan Manajemen Lingkungan, 2018)
The purpose of this study is to reveal the strength of employee's ability factors to understand environmental issues and leadership on the effectiveness of urban forest management employees. This research was carried out in the PT JIEP Pulogadung industrial area in Jakarta for three months, starting from June to August 2017. The research method used was ex post-facto or comparative causal relationship with 2 x factorial design 2. Results of research on urban forest conservation management activities between employees with the ability to understand high environmental issues are higher than those with the ability to understand the low environmental issues. The average urban forest conservation management that has the ability to understand high environmental issues is 141.93 higher than employees who have the ability to understand low environmental issues, namely 125.93. Furthermore, there is an interaction effect between the application of the ability to understand environmental issues and Leadership on the management of forest conservation of the city. The effect of the interaction is 41%. Urban forest conservation management activities between employees who have the ability to understand high environmental issues are higher than employees who have the ability to understand low environmental issues in the group with Transformative Leadership as evidenced from the tuckey test results, that Qcount> Qtable is 5.91> 4 , 11 Keywords: Employee Ability, Environmental Issues, Leadership